2018
DOI: 10.3390/molecules23040907
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Drug Delivery Systems and Anticancer Drugs

Abstract: Cancer is a life-threatening disease contributing to ~3.4 million deaths worldwide. There are various causes of cancer, such as smoking, being overweight or obese, intake of processed meat, radiation, family history, stress, environmental factors, and chance. The first-line treatment of cancer is the surgical removal of solid tumours, radiation therapy, and chemotherapy. The systemic administration of the free drug is considered to be the main clinical failure of chemotherapy in cancer treatment, as limited dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
267
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 462 publications
(272 citation statements)
references
References 103 publications
(123 reference statements)
2
267
0
3
Order By: Relevance
“…Many chemotherapeutic agents have been shown to induce severe systemic toxicity and several side effects due to their deficient pharmacokinetic profiles and non-specific distribution in the body [29]. In Yang et al's study [30], they have encapsulated honokiol into nanopolymers to enhance its permeability and specificity against cancer cells.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Many chemotherapeutic agents have been shown to induce severe systemic toxicity and several side effects due to their deficient pharmacokinetic profiles and non-specific distribution in the body [29]. In Yang et al's study [30], they have encapsulated honokiol into nanopolymers to enhance its permeability and specificity against cancer cells.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Several liposomal drug formulations have been approved in the past 20 years. 16,17 Liposomes protect the encapsulated drugs from structural transformation or chemical degradation by isolating them from the surrounding environment and can provide targeted therapy to tumor cells. 18 It is difficult to formulate the SN38 liposome with high encapsulation efficiency (EE) because of the poor solubility of SN38 and its low affinity to the lipid membrane.…”
Section: Introductionmentioning
confidence: 99%
“…We found that, under these conditions, the loading capacity of each PLT was as high as 15~36 × 10 6 molecules of DOX and identified that loading was at its maximal 6 days after PC collection. This high loading is over 1000fold more than in a 100-nm liposome (10,000~15,000 molecules/liposome) [72], thanks to PLT size and, probably, the unique capacity of entrapment of DOX through the canalicular system [73][74][75]. For ease of clinical treatment, it is important that the PLT formulation can undergo long-term storage.…”
Section: Discussionmentioning
confidence: 99%